Self-Management as an Integral Method of Attention in the Treatment of the Patient with Chronic Kidney Disease - Vázquez-Atanacio, María José (Mexican Journal of Medical Research ICSA, 2018)
Currently, the health care methods for chronic diseases are leaving behind the paternalism and the doctor-patient relationship, giving way to a new model, in which people with any chronic disease play an important role in their own health care with the support of the health care provider, this is called self-management. An important aspect of the self-management of diseases is the determination and elaboration of specific strategies in the patient´s empowerment through knowledge, in order to face all the challenges and demands of living with this disease.